The Role of a Standardized Clinical Care Pathway in Patient Satisfaction and Quality of Life Outcomes after Robotic Assisted Laparoscopic Radical Prostatectomy. Issue 3 (May 2017) - Turini, George A.; Clark, Melissa A.; Machan, Jason; Tucci, Christopher; Renzulli, Joseph F.
Abstract : Introduction: : Clinical care pathways reduce length of stay, variability in practice and costs, yet avoid compromising quality of care or increasing complications. In this study we describe a standardized care pathway, focusing on preoperative and postoperative education as well as immediate postoperative patient care after robotic assisted laparoscopic radical prostatectomy. Methods: : A standardized robotic assisted laparoscopic radical prostatectomy care pathway was introduced at our institution in July 2014. A total of 108 men who underwent robotic assisted laparoscopic radical prostatectomy during 2014 were enrolled in this retrospective chart review and were subsequently mailed a quality of life survey. Data regarding length of stay and number of unplanned calls to the urology office or visits to the emergency department were collected from the chart review. The mailed survey was composed of original questions as well as questions adapted from the FACT‐P (Functional Assessment of Cancer Therapy‐Prostate). Patients who underwent robotic assisted laparoscopic radical prostatectomy between January and June 2014 were compared to those who underwent the same surgery between July and December 2014. Results: : Demographically the 2 cohorts of men who underwent robotic assisted laparoscopic radical prostatectomy were similar. There was a significant reduction in postoperative length of stay in the post‐care pathway cohort. Hospital readmissions were reduced by 75%. Despite earlier discharge home, there was no difference in the number of postoperative calls to the urology office or visits to the emergency department, or in overall patient satisfaction. Conclusions: : The implementation of a standardized care pathway for patients undergoing robotic assisted laparoscopic radical prostatectomy at our institution resulted in a reduced postoperative length of stay and readmission rate. Despite a more rapid discharge from the hospital, patient satisfaction and postoperative quality of life were not negatively impacted.